Evaluation of Eyelander, a Video Game Designed to Engage Children and Young People with Homonymous Visual Field Loss in Compensatory Training. (November 2018) - Waddington, Jonathan; Linehan, Conor; Gerling, Kathrin; Williams, Cathy; Robson, Leonie; Ellis, Richard; Hodgson, Timothy
Introduction: Rehabilitation can improve visual outcomes for adults with acquired homonymous visual field loss. It is unclear, however, whether rehabilitation improves visual outcomes for children because previous training schedules have been tiresome, uninteresting, and have failed to keep them engaged. In this study, we assessed whether children and young people with homonymous visual field loss would adhere to six weeks of unsupervised compensatory training using a specialized video game. Methods: Participants aged between 7 and 25 years with homonymous visual field loss completed tabletop assessments of visual search across four site visits. Two baseline assessments separated by four weeks evaluated spontaneous improvements before training began. Participants were then given a copy of the video game to use unsupervised at home for six weeks. Two follow-up assessments separated by four weeks were then conducted to evaluate immediate and acutely maintained effects of training. Results: Fifteen candidates met the inclusion-exclusion criteria, nine participated, and eight completed the study. Participants completed an average of 5.6 hours of unsupervised training over the six weeks. Improvements on in-game metrics plateaued during week three of training. The time taken to find objects during tabletop activities improved by an average of 24%–95% CI (2%, 46%)—after training. Discussion: The findings demonstrate that children and young people with homonymous visual field loss will engage with gamified compensatory training, and it can improve visual outcomes with less of a time commitment than has been required of adults participating in non-gamified training in previous studies. Appropriately powered, randomized controlled trials are required to evaluate the validity and generalizability of observed training effects. Implications for practitioners: Rehabilitation specialists can use specialist video games and gamification technique to engage children and young people with homonymous visual field loss in long-term unsupervised training schedules.